1991
DOI: 10.1016/0735-1097(91)90735-r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lovastatin on intimal hyperplasia after balloon angioplasty: A study in an atherosclerotic hypercholesterolemic rabbit

Abstract: Restenosis, the major limitation of balloon angioplasty, is the result of intimal hyperplasia after the procedure. Lovastatin, a 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) inhibitor, may influence intimal hyperplasia by lowering serum cholesterol and by blocking deoxyribonucleic acid (DNA) synthesis. To determine whether lovastatin reduces intimal hyperplasia, a prospective, randomized blinded study was performed in 60 atherosclerotic New Zealand White male rabbits. Atherosclerosis was produced by air des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0
2

Year Published

1993
1993
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(40 citation statements)
references
References 63 publications
1
37
0
2
Order By: Relevance
“…Pharmacological approaches, including heparin, calcium antagonists, and angiotensin converting enzyme inhibitors, have been tried with variable success. 39 Lovastatin prevents restenosis in hypercholesterolemic rabbits undergoing femoral balloon angioplasty 19 and reduces restenosis rates after percutaneous transluminal coronary angioplasty in humans. 20 However, it is difficult to extrapolate from these studies any direct effect of vastatins on arterial myocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacological approaches, including heparin, calcium antagonists, and angiotensin converting enzyme inhibitors, have been tried with variable success. 39 Lovastatin prevents restenosis in hypercholesterolemic rabbits undergoing femoral balloon angioplasty 19 and reduces restenosis rates after percutaneous transluminal coronary angioplasty in humans. 20 However, it is difficult to extrapolate from these studies any direct effect of vastatins on arterial myocyte proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Compactin and simvastatin inhibit smooth muscle cell growth in vitro. 16 - 18 Aggressive lipid-lowering treatment with lovastatin prevented restenosis after balloon angioplasty in hypercholesterolemic rabbits 19 and humans. 20 However, no correlations between serum cholesterol and restenosis were found in percutaneous transluminal coronary angioplasty patients.…”
mentioning
confidence: 99%
“…23 We also found that statin use was independently associated with better angiographic and clinical outcome. Although several researchers have found that smooth muscle cell proliferation is inhibited by statin use, 24,25 only a few studies directly investigated the possible effects of this therapy on restenosis after stenting. The present data corroborate the reduction of in-stent restenosis and improved clinical outcome reported by Walter et al 26 in a nonrandomized study of the effects of statins after stenting.…”
Section: Oemrawsingh Et Al Ivus Improves Outcome Of Long Stent Implanmentioning
confidence: 99%
“…Lovastatin is used in the treatment of hypercholesterolaemia and has been shown to prevent restenosis in a hypercholesterolaemic rabbit model of restenosis [9] and in one human coronary restenosis trial [lo]. Lovastatin competitively inhibits 3-hydroxy-3 methylglutaryl-coenzyme A (HMG CoA) reductase [I I], the rate-limiting enzyme in cholesterol biosynthesis.…”
Section: Introductionmentioning
confidence: 99%